2013
DOI: 10.3109/13668250.2013.826346
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition by children with Down syndrome: A longitudinal study

Abstract: The findings indicate that children with DS develop emotion recognition abilities similarly to other children of the same DA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…The lack of difference in this emotion recognition task corroborates Channell et al’s [23] study conducted with children with DS by means of dynamic stimuli (video clips). It also corroborates the study by Pochon and Declercq [24] of children with DS, which made use of static stimuli (photos). On the other hand, the results differ from those observed in earlier studies that used static stimuli, along with emotional vocabulary [9,10,14,15,25] or with dynamic stimuli and production of emotional vocabulary [27].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of difference in this emotion recognition task corroborates Channell et al’s [23] study conducted with children with DS by means of dynamic stimuli (video clips). It also corroborates the study by Pochon and Declercq [24] of children with DS, which made use of static stimuli (photos). On the other hand, the results differ from those observed in earlier studies that used static stimuli, along with emotional vocabulary [9,10,14,15,25] or with dynamic stimuli and production of emotional vocabulary [27].…”
Section: Discussionsupporting
confidence: 90%
“…As in the study by Pochon and Declercq [24], the non-use of emotional vocabulary in the instructions and the formulation of responses undoubtedly avoided certain errors related to insufficient mastery of emotional vocabulary. In this regard, Williams et al [18] emphasized that certain problems experienced by some of the participants in their study might have been related to a poorer understanding of language even though their verbal level was monitored.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These individuals show deficits in recognising facial expressions of fear, surprise, anger, sadness, and a neutral state (Hippolyte, Barisnikov, & Van der Linden, 2008;Hippolyte, Barisnikov, Van der Linden, & Detraux, 2009;Kasari, Freeman, & Hughes, 2001;Porter, Coltheart, & Langdon, 2007;Williams, Wishart, Pitcairn, & Willis, 2005;Wishart & Pitcairn, 2000;Wishart, Cebula, Willis, & Pitcairn, 2007). However, other researchers have not found statistically significant abnormalities in performance on emotion-matching tasks by children with DS (Martínez-Castilla, Burt, Borgatti, & Gagliardi, 2015;Pochon & Declercq, 2013). As far as we know, only one study has included an emotion recognition task in the context of pain assessment of people with intellectual disability (Zabalia & Corfec, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, children with Down's syndrome are not significantly different from other children at emotion recognition tasks ( Pochon and Declercq 2013 ), and show similar developmental trajectories with respect to the acquisition of emotion knowledge ( Channell, Conners, and Barth 2014 ). And a recent survey of health-related quality of life revealed that although children with Down's syndrome score lower than other children on measures of motor skill and cognitive development, they score the same on measures of physical complaints and measures of positive and negative emotions, and they score better (at least in this one survey) on a measure of anxiety and depression ( van Gameren-Oosterom et al 2011 ).…”
Section: Case Two: Intellectual Disabilitymentioning
confidence: 99%